Challenges of Rural Entrepreneurship in the Cumilla District of Bangladesh - Md. Nahid Mia; S. M. Mujahidul Islam; Md. Sahidul Islam (OUSL Journal)
Rural entrepreneurship is a crucial driver of both local and national economic development, often regarded as a key strategy for alleviating unemployment and boosting GDP growth. In recent years, governments have intensified efforts to promote entrepreneurship to address these economic challenges. Despite such initiatives, rural entrepreneurs continue to confront substantial obstacles that hinder their growth and sustainability. This study investigated the challenges faced by rural entrepreneurs in the Cumilla District of Bangladesh, focusing specifically on four agro-based sectors: poultry, nursery, dairy, and fisheries. Primary data were collected from 80 entrepreneurs equally distributed across these sectors, using a structured questionnaire with closed-ended questions measured on a five-point Likert scale. To complement this, secondary sources including academic literature, reports, and media publications were reviewed to establish a comprehensive theoretical framework on rural entrepreneurship. Data analysis was performed using SPSS software, employing descriptive statistics and inferential tests such as means, standard deviations, and t-tests. Additionally, sectoral comparisons were conducted to identify disparities in access to resources and support mechanisms. The study revealed that rural entrepreneurs in Cumilla face critical challenges, including limited capital formation, prohibitive interest rates, inadequate training opportunities for skill and managerial development, and restricted market access and knowledge. However, a key limitation lies in the narrow sectoral focus, as rural entrepreneurship encompasses a far broader spectrum of activities beyond the four agro-based sectors examined.